2011
DOI: 10.1021/tx200113n
|View full text |Cite
|
Sign up to set email alerts
|

γ-Hydroxy-1,N2-propano-2′-deoxyguanosine DNA Adduct Conjugates the N-Terminal Amine of the KWKK Peptide via a Carbinolamine Linkage

Abstract: The γ-hydroxy-1,N2-propano-2′-deoxyguanosine adduct (γ-OH-PdG) was introduced into 5′-d(GCTAGCXAGTCC)-3′·5′-d(GGACTCGCTAGC)-3′ (X = γ-OH-PdG). In the presence of excess peptide KWKK, 13C isotope-edited NMR revealed the formation of two spectroscopically distinct DNA–KWKK conjugates. These involved the reaction of the KWKK N-terminal amino group with the N2-dG propylaldehyde tautomer of the γ-OH-PdG lesion. The guanine N1 base imino resonance at the site of conjugation was observed in isotope-edited 15N NMR exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(175 reference statements)
0
5
0
1
Order By: Relevance
“…DPCs have also been characterized from chemotherapeutic agents such as nitrogen mustards and cisplatin . DPCs can form reversibly with abasic sites or enal adducts of dGuo via Schiff base formation with a lysine side chain or the N-terminal amino group; such DPCs have been reductively trapped.…”
Section: Discussionmentioning
confidence: 99%
“…DPCs have also been characterized from chemotherapeutic agents such as nitrogen mustards and cisplatin . DPCs can form reversibly with abasic sites or enal adducts of dGuo via Schiff base formation with a lysine side chain or the N-terminal amino group; such DPCs have been reductively trapped.…”
Section: Discussionmentioning
confidence: 99%
“…Acrolein creates the hydroxy-l, N 2 -propano-dG adducts, α-and γ-OH-PdG, with γ-OH-PdG being the major product [13]. The γ-OH-PdG adduct may further react with nearby functional groups to form DNA interstrand crosslinks and protein-DNA crosslinks [7072]. Considering the PUFA enrichment of the IMM, α,β-unsaturated aldehydes are likely a major threat to mtDNA stability and gene expression during tissue oxidative stress.…”
Section: Mitochondrial Dna Damagementioning
confidence: 99%
“…8 They further discussed the chemistry of interstrand cross-links induced by unsaturated aldehydes derived from lipid peroxidation and environmental sources. 9 The study of the native DNA−KWKK linkage 10 found that the stabilization of the DNA to thermal denaturation may be improved by carbinolamine-linked DNA− KWKK by intramolecular hydrogen bonding, and theoretical calculation suggests that the carbinolamine-linked DNA− KWKK conjugates exist with the peptide located in the minor groove. For another example, Munõz's group performed some related studies on Schiff base formation in the vitamin B6 system with the aid of theoretical methods.…”
Section: Introductionmentioning
confidence: 99%